A Course of English Language Teaching - Beshlei, Olga (Видавничий дім “РОДОВІД”, 2020)
The study guide is aimed at acquainting students with the "Bachelor" educational level with the didactic, psychological, pedagogical and linguistic principles of teaching English to students of general educational institutions. The study guide covers 14 topics to be studied at lectures and seminars on the "Methodology of Foreign Language Teaching" course. In the theoretical part, the question of characteristics of the main concepts and categories of the discipline is considered, and the main methods and approaches to teaching foreign language material are analyzed. Practical tasks are aimed at developing the methodological skills of future teachers of English. Additional materials include examples of lesson plans, general diagrams and tables. The manual is intended for students of the faculty of foreign languages, school teachers and university professors, as well as for everyone who is interested in teaching English.
ELT